STUDY TO MEASURE MARKET POTENTIAL AND CUSTOMER PURCHASE REASONS - Karina Garcete González, Liz; Lujan Alfonzo Cabañas, Larisa; Gabriel Galeano Rodríguez, Luis; Ariel Téllez Elizeche, Elam; Martínez Martínez, Pamela; Díaz Benítez, Sinecia (Revista Gênero e Interdisciplinaridade, 2023)
Market research refers to a procedure carried out with the intention of investigating the preferences of potential consumers or those interested in certain products or services, with the purpose of obtaining a precise and complete understanding of the panorama that guarantees the making of an informed decision. and correct. The study carried out is designed so that any company that has sales as its main objective can benefit from it by being able to quickly achieve its objectives or goals. This research focuses on analyzing the lack of accurate information about the size and potential of the product market, which often makes strategic decision-making difficult. It is in charge of preparing a market study to learn about new companies and study the rotations of each product line. The methodology used is qualitative research, data collection was carried out through an interview. The results indicate that the study to measure the market potential and the customer’s purchase reason has an impact on new companies and those that wish to enter the market, these companies must carry out a preliminary analysis of the field in which they wish to enter and settle. Themselves their sales plan. In conclusion, to measure market potential and customers’ purchasing motives, it is essential to thoroughly understand the commercial environment and maximize business opportunities. Some key factors that can be obtained from this type of study include: Identification of market segments. This will allow the marketing strategy and product offering to be adapted to meet the needs of each segment more effectively.